Functional and comparative analysis of the FeII/2-oxoglutarate-dependent dioxygenases without using any substrate - Das, Susmita; Shahnaz, Nafeesa; Keerthana, Carmel; Ranjan, Saumya; Seenivasan, Gayathri; Tuti, Nikhil; Shaji, Unnikrishnan P; Meur, Gargi; Anindya, Roy (Biology methods and protocols, 2025)
Non-haem iron (FeII) and 2-oxoglutarate(2OG)-dependent dioxygenases catalyse various biological reactions. These enzymes couple the oxidative decarboxylation of 2OG to the hydroxylation of the substrates. While some of these enzymes are reported to have multiple substrates, the substrate remains unknown for many of the enzymes. However, in the absence of the substrate, these enzymes catalyse oxidative decarboxylation of 2OG and generate succinate. We have determined succinate level to monitor this uncoupled reaction and compared the uncoupled 2OG turnover of different FeII/2OG-dependent dioxygenases. The uncoupled succinate production was used to verify the NiII-mediated inhibition and functionality of human dioxygenase ALKBH6.